Study on the Characteristics of Soil Irrigated by Biogas Slurry in the Southwest of China - Yu, Weiwei; Zhang, Zhi; Luo, Surong; Chen, Shiling (Asian Journal of Chemistry, 2012)
Biogas slurry as quality organic fertilizer is widely used in large scale livestock and poultry farms in the southwest of China. This research used the wastewater from a dairy farm in the southwest, including Grit Chamber wastewater, collection basin wastewater, anaerobic tank wastewater, aerobic effluent and clean water for parallel irrigation in the greenhouse. The results indicate that anaerobic tank wastewater contains the maximum ammonia nitrogen content of 860 mg/kg in 0-5 cm soil profile sample. In 0-5 cm soil profile samples, the content of nitrate nitrogen in anaerobic tank wastewater remains the highest 23.95 mg/kg. In 5-10 and 10-20 cm soil profile samples, the nitrate nitrogen content of the other four test groups increase and reach the final value of 23.67 mg/kg. In 0-5 cm from soil surface the phosphorus content of the five groups are less than 100 mg/kg. The phosphorus absorption coefficient of clean water reaches a peak value of 570 after a month. In the test of soil carrying capacity, the maximum content of ammonium nitrogen, nitrate and available phosphorus are 1355, 24.65 and 163.66 mg/kg, respectively. The phosphorus absorption coefficient within 21-25 days goes above 500. Scanning electron microscopy analysis shows that, after long-term biogas slurry irrigation, the soil porosity and microorganism adherent to the clusters increase, resulting in improvement of the stability of the soil.